LITERATURE REVIEW: THE EFFECTIVENESS OF SUPPORTIVE GROUP THERAPY IN FAMILY WITH EARLY ADULTS WITH ANXIETY IN THE QUARTER-LIFE CRISIS - Bagus Dwi Cahyono; Nurul Huda; Evy Aristiawati; Septian Yoga Permana (UPT Penerbitan Universitas Jember, 2023)
Background: In the age range of 18-29 years, generally early adults experience anxiety that arises during the quarter life crisis phase. Anxiety arises with increasing age because individuals experience several pressures from various parties, both demands from the environment, demands from family to demands from themselves. Supportive group therapy will make a place for individual mental healing because individuals with the same problem will strengthen each other and share experiences in the group, Methods: The Method used is a literature review by reviewing 5 international articles and 5 national articles, the data collection process using the PRISMA (Preferred Reporting Items For Review and Meta Analysis) method and data analysis using Thematic Analysis to examine articles using compare, contrast and criticize., Results: The results showed that 10 articles stated that supportive group therapy was significantly able to reduce anxiety. Anxiety decreases due to mutual reinforcement of members in a supportive group, Conclusions: The conclusion of the author states that supportive group therapy can be used as a nursing intervention to reduce anxiety in early adults who experience anxiety during the quarter life crisis.